2015
DOI: 10.1101/025056
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A statistical approach reveals designs for the most robust stochastic gene oscillators

Abstract: The engineering of transcriptional networks presents many challenges due to the inherent uncertainty in the system structure, changing cellular context, and stochasticity in the governing dynamics. One approach to address these problems is to design and build systems that can function across a range of conditions; that is they are robust to uncertainty in their constituent components. Here we examine the parametric robustness landscape of transcriptional oscillators, which underlie many important processes suc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…We find that the parameters representing the rates of degradation of the transcription factors in the system (k x ,k y ) must both be large in relation to the prior range, and approximately equal, for bistability to occur. Protein degradation rates have been shown to be important for many system behaviours including oscillations [7,56,57]. We also find that the steady states of the LU-CS model are symmetric: the values for the dominant and repressed species are equivalent in both steady states.…”
Section: Repressor Degradation Rates Are Key For Achieving Bistablitymentioning
confidence: 52%
“…We find that the parameters representing the rates of degradation of the transcription factors in the system (k x ,k y ) must both be large in relation to the prior range, and approximately equal, for bistability to occur. Protein degradation rates have been shown to be important for many system behaviours including oscillations [7,56,57]. We also find that the steady states of the LU-CS model are symmetric: the values for the dominant and repressed species are equivalent in both steady states.…”
Section: Repressor Degradation Rates Are Key For Achieving Bistablitymentioning
confidence: 52%
“…Note that, we used the lumped propensity functions derived from the reduced model, like the f (n i 3 , t) Hill-like function associated with LuxI repression. This approach has already been used in [53]. We validated it for our model (see Appendix I) by simulating the pseudoreaction associated with f (n i 3 , t) using the CLE approach and comparing the result with the one obtained by simulating the expanded set of corresponding original reactions using the Gillespie's direct method Stochastic Simulation Algorithm (SSA).…”
Section: Stochastic Modelmentioning
confidence: 99%
“…Following an approach used in [53], we validated the use of a high-order propensity function by simulating the pseudoreaction associated with f (n 3 , t) using the CLE approach and then comparing this result with the one obtained by simulating the set of corresponding original reactions using the Gillespie's direct method SSA.…”
Section: Appendix I Nonlinear Propensitiesmentioning
confidence: 99%
“…Theoretical studies on the topological designs of biological oscillators (Tsai et al, 2008;Woods et al, 2016) have suggested that the positive feedback loops may play an important role in the robustness and great tunability of an oscillator. Modeling of the cell cycle network has also highlighted the essential role of Cdk1/Wee1/Cdc25 positive feedback in the cell cycle behavior as a relaxation oscillator, which provided an explanation why the cell cycle is highly tunable in frequency (Tsai et al, 2008;Gérard et al, 2012).…”
Section: Introductionmentioning
confidence: 99%